DIVERSITY AND DISTRIBUTION OF MACROALGAE TO ENVIRONMENTAL CONDITIONS OF MAKASSAR CITY - Mushlihah, Hidayah; Faizal, Ahmad; Amri, Khairul (Jurnal Ilmu Kelautan SPERMONDE, 2021)
The distribution of macroalgae in the waters is influenced by various environmental factors ranging from anthropogenic pressures such as the activities of local communities and tourists to the Physico-chemical effects of the waters. This study aims to examine the effect of environmental parameters on the distribution of macroalgae and to map the spatial distribution of macroalgae on Lae-lae Island and Gusung Lae-lae Caddi. Data collection for macroalgae was carried out using a 1 × 1 m transect method and environmental parameters were surveyed using in situ measurements and further analysis in the laboratory. The status and diversity of macroalgae were calculated using ecological indices, distribution of macroalgae using Mapping Techniques, and the interrelationships between parameters were tested using Principal Component Analysis (PCA). The results showed that the largest macroalgae cover was found in Gusung Lae-Lae Caddi by 55% with the average distribution of macroalgae cover respectively; Lae-laen Island East Station 9%, Lae-lae Island West Station 36%, Gusung Lae-lae Caddi East Station 21%, and Gusung Lae-lae Cadii West Station 55%. The high macroalgae cover in Gusung Lae-Lae Caddi is influenced by nutrients and the low level of turbidity. Based on the calculation of the ecological index, it was found that the ecological status was dominated by the late-successional group.